Integron Involvement in Environmental Spread of Antibiotic Resistance - Stalder, Thibault; Barraud, Olivier; Casellas, Magali; Dagot, Christophe; Ploy, Marie-Cecile (Frontiers in Microbiology, 2012)
The spread of antibiotic-resistant bacteria is a growing problem and a public health issue. In recent decades, various genetic mechanisms involved in the spread of resistance genes among bacteria have been identified. Integrons -- genetic elements that acquire, exchange and express genes embedded within gene cassettes (GC) -- are one of these mechanisms. Integrons are widely distributed, especially in Gram-negative bacteria; they are carried by mobile genetic elements, plasmids and transposons, which promote their spread within bacterial communities. Initially studied mainly in the clinical setting for their involvement in antibiotic resistance, their role in the environment is now an increasing focus of attention. The aim of this review is to provide an in-depth analysis of recent studies of antibiotic-resistance integrons in the environment, highlighting their potential involvement in antibiotic resistance outside the clinical context. We will focus particularly on the impact of human activities (agriculture, industries, wastewater treatment, etc.).